A label-free and signal-on electrochemical aptasensor for ultrasensitive kanamycin detection based on exonuclease recycling cleavage. Issue 4 (22nd December 2015) - Xu, Yuanyuan; Sun, Linghao; Huang, Xiaocui; Sun, Yangyang; Lu, Chenhe
Abstract : A label-free and signal-on electrochemical aptasensor for kanamycin detection has been proposed based on aptamer triggered Exo III recycling cleavage. Abstract : Taking advantage of the preferential exodeoxyribonuclease activity of exonuclease III (Exo III) in combination with the highly specific recognition of aptamers, a label-free and signal-on electrochemical aptasensor for ultrasensitive kanamycin (Kan) detection has been proposed based on aptamer triggered Exo III recycling cleavage. Aptamer complementary DNA (cDNA) with a 5′ thiol group is self-assembled onto a gold electrode surface for the following hybridization with a kanamycin specific aptamer (K-aptamer). The formed duplex DNA has 3′ hydroxyl blunt termini as a recognition element, and cDNA could be stepwise removed by Exo III ultimately resulting in the release of the K-aptamer for successive new cycles of hybridization and cleavage. Upon sensing the analyte, the combination of Kan and K-aptamer impedes the cleavage process catalyzed by Exo III, and the retained cDNA is proportional to the concentration of Kan, which is electrochemically quantified via the adsorption of RuHex. Due to the high sensitivity of the electrochemical method and the recycling signal amplification of Exo III, the proposed aptasensor can detect Kan down to a 1 pM level. More importantly, it is label-free, signal-on and surface-tethered, which make this biosensor more suitable and stable for the application of Kan detection in real samples.